Emotional intelligence and physical activity among Malaysian adolescents - Omar Dev, Roxana Dev; Ismail, Ismi Arif; Abdullah, Maria Chong; Soh, Kim Geok (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
As we all know the benefits of physical activity (PA) on physical and mental health are well established. However, inactivity among adolescents in Malaysia is still prevalent. This study examined whether emotional intelligence (EI) was one of the underlying psychological mechanisms that may associated with the current low levels of PA adherence. Therefore, the purpose of the study was to examine whether EI plays a role as the potential underlying mechanism of PA behavior among Malaysian adolescents in secondary schools. A total of 270 sixteen year old students were recruited from a few Malaysian secondary schools. It was found that students with higher physical activity (among those who are school athletes) in a week had better total EI scores and composite subscale scores. The findings of this study provide further support claims that there is a positive relationship between increased levels of EI and physical activity. Thus, the importance of higher emotional intelligence skills is seen to be one of the upmost important agenda that should be looked at in public schools to help on promoting exercise and physical activity participation. It is highly recommended that the programs should be targeted at the maximum level towards individual who were sedentary and low active.